Cerebral venous thrombosis - Moraes, Anisio Adalio de Azevedo, Junior; Conforto, Adriana Bastos (Arquivos de Neuro-Psiquiatria, 2022)
Cerebral venous sinus thrombosis (CVT) consists of partial or complete occlusion of a sinus or a cerebral vein. CVT represents 0.5-1% of all strokes and is more frequent in young women. This review discusses particular aspects of CVT diagnosis and management: decompressive craniectomy (DC), anticoagulation with direct oral anticoagulants (DOACs), CVT after coronavirus-disease 19 (COVID-19) and Vaccine-Induced Immune Thrombotic Thrombocytopenia (VITT).
Keywords: Sinus Thrombosis, Intracranial; Decompressive Craniectomy; COVID-19; COVID-19 Vaccines.